Egg quality evaluation of japanese quail (Coturnix coturnix japonica) supplemented with powdered leaves of jute mallow (Corchorus olitorius) and siam weed (Chromolaena odorata) - Gemma M Guigue; Alejandro Jr B Dianon; Decem Mary Joice D Tolero (BIO Web of Conferences)
The study aimed to evaluate the egg quality of Japanese quail (Coturnix coturnix japonica) supplemented with powdered leaves of jute mallow and Siam weed. A total of 144 quail eggs were collected and evaluated every Thursday over six weeks using a Complete Randomized Design (CRD). The experimental treatments included four formulations (T1 to T4) combining commercial rations with varying levels of jute mallow and Siam weed leaf powders. Parameters assessed were egg weight, egg width, eggshell weight, eggshell thickness, eggshell strength, egg length, yolk weight, albumen weight, and yolk color, which were analyzed using oneway analysis of variance (ANOVA). The results indicated no significant differences in most egg quality parameters, including egg weight, egg width, eggshell weight, eggshell thickness, eggshell strength, egg length, yolk weight, and albumen weight, among treatments. However, yolk color exhibited a highly significant difference, with quails fed the supplemented rations showing an improved yolk color rating. These findings suggest that incorporating powdered jute mallow and Siam weed leaves into quail diets enhances yolk color, making it a viable natural colorant alternative. This practice is recommended as it utilizes locally available, cost-effective resources rich in nutrients beneficial for egg production. Additionally, the supplementation stimulates the digestive system, enhancing digestive enzyme production and feed utilization efficiency by improving liver function, as supported by [7]. Using such natural feed additives aligns with sustainable agricultural practices, offering a practical and environmentally friendly solution for improving specific aspects of egg quality, particularly yolk pigmentation, in laying quails.